2019
DOI: 10.3389/fgene.2019.00194
|View full text |Cite
|
Sign up to set email alerts
|

Utility of cfDNA Fragmentation Patterns in Designing the Liquid Biopsy Profiling Panels to Improve Their Sensitivity

Abstract: Genotyping of cell-free DNA (cfDNA) in plasma samples has the potential to allow for a noninvasive assessment of tumor biology, avoiding the inherent shortcomings of tissue biopsy. Next generation sequencing (NGS), a leading technology for liquid biopsy analysis, continues to be hurdled with several major issues with cfDNA samples, including low cfDNA concentration and high fragmentation. In this study, by employing Ion Torrent PGM semiconductor technology, we performed a comparison between two multi-biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…For most of the cancer hallmarks, their effects on ctDNA release are still unknown, and the direct cause of ctDNA shortening has not been clearly demonstrated (Hanahan and Weinberg, 2011). Leveraging the Genome-wide Fragmentation of cfDNA Boosts Liquid Biopsy Despite these unknowns, the genome-wide fragmentation of cfDNA can be leveraged to boost existing methods and unlock new applications for liquid biopsy (Ivanov et al, 2015(Ivanov et al, , 2019Mouliere et al, 2018a;Snyder et al, 2016) (Figure 4B and Table 1). Mouliere et al developed a machine-learning method that can learn from the genome-wide fragmentation features of cfDNA to detect multiple cancer types in plasma (Mouliere et al, 2018a).…”
Section: Decoding the Structural Fingerprints Of Cfdnamentioning
confidence: 99%
“…For most of the cancer hallmarks, their effects on ctDNA release are still unknown, and the direct cause of ctDNA shortening has not been clearly demonstrated (Hanahan and Weinberg, 2011). Leveraging the Genome-wide Fragmentation of cfDNA Boosts Liquid Biopsy Despite these unknowns, the genome-wide fragmentation of cfDNA can be leveraged to boost existing methods and unlock new applications for liquid biopsy (Ivanov et al, 2015(Ivanov et al, , 2019Mouliere et al, 2018a;Snyder et al, 2016) (Figure 4B and Table 1). Mouliere et al developed a machine-learning method that can learn from the genome-wide fragmentation features of cfDNA to detect multiple cancer types in plasma (Mouliere et al, 2018a).…”
Section: Decoding the Structural Fingerprints Of Cfdnamentioning
confidence: 99%
“…Both ALU and LINE1 sequences are distributed throughout the genome. In recent years, both n-cfDNA and mt-cfDNA have been used to examine mutations, methylation, copy-number variations (CNVs), cfDNA composition, and cfDNA fragmentation [97][98][99][100][101]. Some molecular biology techniques have been used to analyze cfDNA from plasma samples, including fluorescence [15], polymerase chain reaction (PCR) [9,14], quantitative real-time PCR (RT-qPCR) [16,[102][103][104][105][106][107][108][109][110], droplet digital PCR (ddPCR) [87,[111][112][113][114][115][116], array [111,117] and sequencing [86,[105][106][107]113,[117][118][119][120][121][122][123][124][125][126][127].…”
Section: Cfdna-molecular Featuresmentioning
confidence: 99%
“…Integrating cfDNA fragmentomic information has already been shown to improve testing sensitivity in noninvasive cancer diagnostics and screening. 92,93 One of the major hurdles in prenatal screening is the accurate determination of the fetal fraction. This review has touched upon several identified fragmentomic markers that can be used to approach the fetal fraction, or more generally, to determine the maternal or fetal origin of variants observed using NIPT.…”
Section: Discussionmentioning
confidence: 99%